(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Forensic Medicine, an essential component of medical education, has witnessed a declining interest among medical students as a postgraduate specialty choice. This research aims to develop a questionnaire to assess the attitude of medical students and interns towards Forensic Medicine and conduct a pilot study to test its validity and reliability. The study setting was at a tertiary medical institute in Northeast India, and the subjects included medical students and interns. Convenience sampling was used, and the data were analyzed using Microsoft Excel and SPSS. The results indicate a neutral-to-positive attitude towards Forensic Medicine as an interesting specialty while considering it as a career option remains uncertain. Cronbach’s Alpha demonstrated acceptable reliability for the questionnaire. Further studies with larger sample sizes and multi-centric approaches are recommended to gain more comprehensive insights. Enhancing integration with other subjects, providing clinical forensic medicine training, and creating research opportunities could foster interest and potential career choices in Forensic Medicine.